Giant torus mandibularis causing submandibular duct obstruction and sialadenitis. Issue 3 (June 2021) - Madhavan, Ajay A; McDonald, Robert J; Diehn, Felix E; Carr, Carrie M; Verdoorn, Jared T
Torus mandibularis is a benign osseous overgrowth arising from the lingual surface of the mandible. It is a common, incidental finding on imaging due to its relatively high prevalence. In the majority of cases, mandibular tori are asymptomatic. We report a novel presentation of a giant torus mandibularis causing bilateral obstruction of the submandibular ducts and consequent sialadenitis. Our patient presented with progressive pain centered in the floor of his mouth and had bilateral submandibular glandular enlargement on exam. Computed tomography showed a giant right torus mandibularis, which was causing obstruction and dilation of the bilateral submandibular ducts. Although conservative management was attempted, he ultimately underwent surgical resection of his torus with symptomatic improvement. This patient highlights a novel complication of torus mandibularis and illustrates successful treatment. Though not previously described, this complication may be underreported and should be considered in the appropriate clinical setting.